THE “LASEPRF”- LASER TREATED PRF FOR TREATMENT OF MULTIPLE GINGIVAL RECESSIONS - A CASE REPORT - Keerthi.K.L,; P.Aravind Kumar,; M. Narendra Babu,; K.Raviraj, (Journal of Biomedical and Pharmaceutical Research, 2020)
Treatment of gingival recession has become an important therapeutic issue due to increasing cosmetic demand. Multiple surgical procedures have been developed to obtain predictable esthetic root coverage.. Low level laser therapy (LLLT) has biostimulative effect on platelets by inducing platelet degranulation. Therefore, it can be possible that the use of Platelet rich fibrin (PRF) treated with LLLT could help in increasing the concentration of growth factors in the wound healing, thus accelerates healing process. This paper reports the use of PRF treated with laser for root coverage on the labial surfaces of the maxillary right teeth.Keywords: Low level laser therapy (LLLT), Platelet rich fibrin (PRF), Modified VISTA technique.